MIGRASI DALAM PERUBAHAN SOSIAL EKONOMI MASYARAKAT DESA TALANGO - Fajrin Nurul Qomariya; Hadi Soetarto; Nur Inna Alfiyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2021)
AbstractPopulation migration is an integral part of the development process in Indonesia. Thephenomenon of migration that does not take place within a country is widely seen in variousregions of Indonesia, each region certainly has different characteristics and each region hasnatural resources and human resources. which are not equal in number, this differencecauses the distribution of the population to be uneven and also a change in mindset that isnot in accordance with what is desired.This study aims to describe an economic condition of the Talango village communitycaused by migration, which of course gives a good influence on an economic condition interms of social and development in Talanago village.The results of this study in the title Migration in Changes in Socio-EconomicConditions of the Talango Village Community, which describe several conclusions that havebeen studied and analyzed using the theory of Everett, S Lee 1970 in Purwanto, (2007: 2017)there are three factors that need to be considered in the process. population migration,among others, positive factors, negative factors, neutral factors discussion that can be takenfrom this research are as follows: positive factors where the population because someonewants to change their standard of living for the better, economic factors are the drivingfactors that people migrate to leave their place of residence development, the availability ofjobs and opportunities to earn higher incomes are very accurate attractors in changingsocio-economic conditions, and also higher opportunities to obtain education becomeattractive as migrant actors as students, favorable environmental conditions provide apattern of life. up who live a prosperous life, and where progress at the destination is one ofthe most important accesses seen by migrant actors, while neutral factors are real factorsthat exist at the place of origin or destination are not yet the main factors, because in the endit returns to the response someone about these factors, personal sensitivity and intelligence,every time you make a decision from yourself there must be obstacles or obstacles there are anumber of factors that keep people from staying there, and attract outsiders to move to thatplace, there are a number of negative factors that encourage people to move from the place.Keywords: Migration, Driving Factors for Migration